Morphological Characters and Needle Anatomical of some Pine Species in EL-Jabal EL-Akhdar Region, East Libya (Libyan Journal of Ecological & Environmental Sciences and Technology, 2021)
In this  research , we studied the morphological and needle anatomical traits for six pine species : Pinus halepensis,P. brutia , P. pinea, P. nigra,P. canariensis and P. merkusii at different altitudes in EL-Jabal EL-Akhdar region east-Libya. The results indicated a significant means  difference of some traits  between species  . P. canariensis was the longest needle and cone 28.53,14.11 cm, respectively.  while P.merkusii was the shortest needle 5.9 cm and the smallest cone. P. brutia was distinguished by the shortest seed of 0.511 cm and the longest wing of 2.38 cm .P. Pinea was distinguished by the longest seed of 1.75 cm and the shortest wing of 0.5 cm and the cone width of 6.71 cm, and the needle diameter was larger than the other species 1.89 mm . On the other hand, the center of the needle for all coniferous species  have two vascular bundles, and therefore these species are classified under the Diaploxylon section. These  traits are importan for creating an identifying key for El-JabalEl-Akhdar conifers.
Keywords: Pine; anatomy; morphology; needle; EL-Jabal EL-Akhdar